2019
DOI: 10.3390/biom9060237
|View full text |Cite
|
Sign up to set email alerts
|

A Novel View of Human Helicobacter pylori Infections: Interplay between Microbiota and Beta-Defensins

Abstract: The gut microbiota is significantly involved in the preservation of the immune system of the host, protecting it against the pathogenic bacteria of the stomach. The correlation between gut microbiota and the host response supports human gastric homeostasis. Gut microbes may be shifted in Helicobacter pylori (Hp)-infected individuals to advance gastric inflammation and distinguished diseases. Particularly interesting is the establishment of cooperation between gut microbiota and antimicrobial peptides (AMPs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 134 publications
(156 reference statements)
3
42
0
Order By: Relevance
“…Over the course of the experiment, the two groups began to separate ( P = .083 at 3 months and P = .006 at 6 months) 48 . This indicated that the time period for acquiring H pylori infection may be another factor in the divergence for microbiome alterations with H pylori infection 49 . Besides, the gut microbiota could be influenced by other factors such as exercise and host genome 50,51 .…”
Section: Discussionmentioning
confidence: 97%
“…Over the course of the experiment, the two groups began to separate ( P = .083 at 3 months and P = .006 at 6 months) 48 . This indicated that the time period for acquiring H pylori infection may be another factor in the divergence for microbiome alterations with H pylori infection 49 . Besides, the gut microbiota could be influenced by other factors such as exercise and host genome 50,51 .…”
Section: Discussionmentioning
confidence: 97%
“…The other topic which deserves more attention is HPI-associated dysregulation of gut microbiota [ 239 , 606 , 653 , 654 , 655 , 656 , 657 , 658 , 659 , 660 , 661 , 662 , 663 , 664 , 665 , 666 , 667 ], a phenomenon described also in animal models (infected Mongolian gerbils [ 668 ]) and thought to be due mainly to gut immunopathological/inflammatory responses and suppressed gastric acid secretion following chronic/atrophic gastritis or use of acid-suppressive drugs. Gut dysbiosis by affecting various biological processes contributes to the pathogenesis of OP [ 669 , 670 , 671 , 672 , 673 , 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 ] as well as to numerous other extra-digestive system diseases associated with OFs [ 700 , 701 , 702 ,…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…The third comprises the neutralization of the activity of MprF; as a consequence, there is a decrease in the infectious activity by S. aureus, making it more accessible to treatment with lipopeptide antibiotic daptomycin [131]. In addition, cyclization and analog engineering increase the stability of different AMPs enclosing human defensins [131][132][133][134][135][136][137][138][139][140][141]. This process improves their therapeutic efficacy; as a result, a greater susceptibility by S. aureus is observed, thus causing the disappearance of skin infections.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%